The swerve : how the world became modern - Greenblatt, Stephen, 1943- (New York : W.W. Norton, 2011)
Nearly six hundred years ago, a short, genial, cannily alert man in his late thirties took a very old manuscript off a library shelf, saw with excitement what he had discovered, and ordered that it be copied. That book was the last surviving manuscript of an ancient Roman philosophical epic, On the Nature of Things, by Lucretius, a beautiful poem of the most dangerous ideas: that the universe functioned without the aid of gods, that religious fear was damaging to human life, and that matter was made up of very small particles in eternal motion, colliding and swerving in new directions. The copying and translation of this ancient book fueled the Renaissance, inspiring artists such as Botticelli and thinkers such as Giordano Bruno; shaped the thought of Galileo and Freud, Darwin and Einstein; and had a revolutionary influence on writers such as Montaigne and Shakespeare and even Thomas Jefferson.
The book hunter -- The moment of discovery -- In search of Lucretius -- The teeth of time -- Birth and rebirth -- In the lie factory -- A pit to catch foxes -- The way things are -- The return -- Swerves -- Afterlives.
Includes bibliographical references (p. [309]-335) and index.
National Book Award, 2011.
Keywords: Lucretius Carus, Titus -- Influence; Lucretius Carus, Titus; Renaissance; Philosophy, Renaissance; Science, Renaissance; Civilization, Modern